Tanggung Gugat Perusahaan Reasuransi Atas Pelanggaran Prinsip Itikad Baik Dalam Pembayaran Klaim Kepada Perusahaan Asuransi - Maulida, Talia Alfirna; Chumaida, Zahry Vandawati (UNES Law Review, 2023)
Article 1 point 7 of Undang-Undang Nomor 40 Tahun 2014 concerning Insurance explains that the reinsurance business is a reinsurance service business for insurance companies, guarantee companies, or other reinsurance companies for the risks faced by these companies. The implementation of reinsurance is stated in a reinsurance agreement based on the principle of utmost good faith. In practice, the parties often violate the principle of utmost good faith, such as in the case between PT Asuransi Tugu Kresna Pratama and PT Agilent Risk Specialties and PT MAA General Insurance. PT Agilent Risk Specialties and PT MAA General Insurance do not pay claims and fulfil their obligations as reinsurance brokers and reinsurers. There is a violation of the principle of utmost good faith, which should have been the basis of the implementation of the reinsurance agreement. This event forms the basis of this research, namely formulating legal arguments with systematic results regarding legal rules relating to reinsurance company liability for violations of the principle of good faith in paying claims to insurance companies.